Engaging the community in educational and social amelioration: lessons and prospects - Hlalele, Dipane; Tsotetsi, Cias (CSSALL, 2015)
A crucial element to ensure the success of a project is the community’s engagement in it: in other words, the participation of individuals, community-based organisations and institutions that would be affected by the endeavour is vital to its success. Studies suggest that strong community participation during a programme’s development and implementation is more likely to assure its long-term viability. There has been a proliferation of academic programmes that embrace community involvement, service-learning and volunteerism flowing from the understanding that community engagement constitutes one of the core functions in South African higher education. Universities attempt in their own ways to engage students in various projects and programmes to make them aware of the role that a university has to play in the social and economic development of the surrounding community. This paper reports on the lessons and prospects emanating from free attitude interviews (FAI) with five mathematics and science students, members of a non-governmental organisation (Pula) and a number of beneficiaries. Findings indicate that it is essential to craft a common purpose between the university, NGOs and beneficiaries. Youth educators also indicated that they derived a heightened sense of accomplishment when addressing challenges experienced by their peers.
Keywords: Free attitude interviews; Community engagement; Social capital; Participatory action research; Pre-service teachers